2000
DOI: 10.1097/00005131-200006000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Intertrochanteric-Subtrochanteric Fractures: Treatment With the Long Gamma Nail

Abstract: Closed reduction and long Gamma nailing of intertrochanteric-subtrochanteric fractures enables the orthopaedic surgeon to treat these fractures with a minimally invasive procedure and a negligible rate of mechanical complications. The rate of union was 100 percent in this series. The rate of restitution to the preinjury status was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 14 publications
5
44
1
8
Order By: Relevance
“…The advantages of the endomedullary nail are lesser blood loss and a lower percentage of failures, the latter being essential in order to avoid reinterventions that pose an important risks for the elderly patient [12,15,17]. On the other hand, the consolidation rate obtained is high (with only one case of pseudoarthrosis in our series), and with the use of short nails one of the most common complications in endomedullary nailing procedures is diminished: diaphyseal refracture fundamentally associated with the use of long gamma-nails (not seen in our series) [13]. Failure of closed fracture reduction is relatively infrequent, since perfect anatomical reduction is not necessary for implantation, the consolidation can be achieved provided that there is sufficient contact between the bone fragments.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The advantages of the endomedullary nail are lesser blood loss and a lower percentage of failures, the latter being essential in order to avoid reinterventions that pose an important risks for the elderly patient [12,15,17]. On the other hand, the consolidation rate obtained is high (with only one case of pseudoarthrosis in our series), and with the use of short nails one of the most common complications in endomedullary nailing procedures is diminished: diaphyseal refracture fundamentally associated with the use of long gamma-nails (not seen in our series) [13]. Failure of closed fracture reduction is relatively infrequent, since perfect anatomical reduction is not necessary for implantation, the consolidation can be achieved provided that there is sufficient contact between the bone fragments.…”
Section: Discussionmentioning
confidence: 61%
“…The decision to adopt the Gamma3 Nail as our implant in this type of fractures was based on the findings of last year´s studies between the previous gamma-nail and the Gamma3, in which the Gamma3 afforded the best results [18][19][20][21][22][23][24]. We agree with most authors that the best way to prevent complications is to ensure a careful surgical technique, with special attention to medullary cavity drilling and the manual insertion of the nail [13] In our study we recorded a single cutting phenomenon, in contrast to the 6% rate reported in another series reviewed in our hospital, involving 348 trochanteric fractures treated with the short gamma-nail, and where 37% were A.2 type fractures. This could, in part, be related to an improved surgical technique as well as the increased stability afforded by the long gamma3-nail, due to its lesser leverage and increased length [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the number of lengths available for long versions would not be suitable for all femurs from the greater trochanter to the condylar notch, the routine use of long IMNs for the fixation of proximal femoral fractures seems logical for splinting the maximum length of the bone. However, the indications for choosing either a standard or long IMN are somewhat unclear and usually subjective [2], and it is unclear whether long nails reduce the rates of reoperation and nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Intramedullary nailing to incorporate fixation of the femoral neck and head has advantages, namely shorter operating times and less blood loss, as well as lower rates of infection, non-union, and implant failure. [16][17][18] Plating is still recommended for fractures with proximal trochanteric extension, especially when medial cortical contact can be restored. 3,19,20 We aimed to compare closed intramedullary nailing without anatomic reduction to open reduction and internal fixation using a fixed angle device for subtrochanteric femoral fractures.…”
Section: Introductionmentioning
confidence: 99%